Concession contract renegotiations : some efficiency versus equity dilemmas - Estache, Antonio 1957- (Policy research working paper, 2001)
If having firm-driven renegotiations of contracts for infrastructure services is a major concern, efficiency should not be the only consideration in selecting an operator, indeed, consumers may want to award the concession to a less efficient firm if that would reduce the probability of renegotiation